Traumatic Brain Injury Modifies the Relationship Between Physical Activity and Global and Cognitive Health: Results From the Barcelona Brain Health Initiative - Morris, Timothy P.; Tormos Muñoz, Jose-Maria; Cattaneo, Gabriele; Solana-Sánchez, Javier; Bartrés-Faz, David; Pascual-Leone, Alvaro (Frontiers in Behavioral Neuroscience, 2019)
Physical activity has many health benefits for individuals with and without history of brain injury. Here we evaluated in a large cohort study the impact of physical activity on global and cognitive health as measured by the PROMIS global health and NeuroQoL cognitive function questionnaires. A nested case control study assessed the influence of a history of traumatic brain injury (TBI) on the effects of physical activity since underlying pathophysiology and barriers to physical activity in individuals with TBI may mean the effects of physical activity on perceived health outcomes differ compared to the general population. Those with a history of TBI (n=81) had significantly lower Global health (=-1.66, p=.010) and NeuroQoL cognitive function (=-2.65, p=.006) compared to healthy adults (n=405). A similar proportion of individuals in both groups reported being active compared to being insufficiently active (X2 (1) = .519 p = .471). Furthermore, the effect of physical activity on global health (=.061, p=.076) and particularly for NeuroQoL (=.159, p=.002) was greater in those with a history of TBI. Individuals with a history of TBI can adhere to a physically active lifestyle, and if so, that is associated with higher global and cognitive health perceptions. Adhering to a physically active lifestyle is non-trivial, particularly for individuals with TBI, and therefore adapted strategies to increase participation in physical activity is critical for the promotion of public health.